2015
DOI: 10.1039/c5ee00835b
|View full text |Cite
|
Sign up to set email alerts
|

Methods of photoelectrode characterization with high spatial and temporal resolution

Abstract: This article reviews computational and in situ experimental tools capable of characterizing the properties and performance of photoelectrodes used for solar fuels production with high spatial and temporal resolution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 307 publications
(384 reference statements)
0
47
0
Order By: Relevance
“…As a probe to study surfaces and interfaces under real conditions, surface-sensitive optical spectroscopy is highly desirable, yet only very few methods with the required spatial resolution are applicable in growth environment or electrochemistry [17,18]. RAS is such an optical technique, probing the anisotropy of a surface at very high surface sensitivity [19], and with additional high in-plane resolution in the case of RA microscopy [20].…”
Section: Introductionmentioning
confidence: 99%
“…As a probe to study surfaces and interfaces under real conditions, surface-sensitive optical spectroscopy is highly desirable, yet only very few methods with the required spatial resolution are applicable in growth environment or electrochemistry [17,18]. RAS is such an optical technique, probing the anisotropy of a surface at very high surface sensitivity [19], and with additional high in-plane resolution in the case of RA microscopy [20].…”
Section: Introductionmentioning
confidence: 99%
“…Transient absorption spectroscopy (TAS) can directly monitor the dynamics of photogenerated charge carriers. 24 During the past few years, the dynamics of photogenerated charge carriers in hematite with and without surface modification were intensively studied by Durrant's group, [25][26][27][28][29][30][31][32][33] mainly on a time scale of ms-s, which demonstrated that photocurrents were related to photogenerated long-lived holes, 27 and surface modification formed a hetero-conjunction at the surface of hematite films, [28][29][30] thus instead of recombining with photogenerated electrons, surface modification promoted the transfer of holes onto the surface to oxidize water. An ultrafast (fs-ns) TAS study was also undertaken by the same group to explore the effect of applied bias on the ultrafast electron-hole recombination.…”
Section: Introductionmentioning
confidence: 99%
“…Spatial resolution—often at the cost of temporal resolution—can also be achieved by various scanning probe techniques such as scanning photocurrent microscopy or electrochemical scanning tunneling microscopy . These techniques do, however, often have the disadvantage of a very limited temporal resolution, which impairs in situ control during surface processing.…”
Section: The Solid–liquid Interfacementioning
confidence: 99%
“…Paired with a detailed understanding of interface formation mechanisms, however, the true power of in situ control is to allow for specific modification and tuning of interface formation for the device of choice. There are several excellent reviews on in situ approaches covering wide ranges of materials from basic science to applications as well as varieties of preparation and analysis techniques . As indicated in Figure , this review will be focused on in situ control over interfaces of materials that are relevant for photoinduced reactions in high‐efficiency solar energy conversion and sensing applications with in situ control of semiconductor/polymer/biological interfaces.…”
Section: Introductionmentioning
confidence: 99%